Leaving 'Sarmatian salt-mines' or theology of science in action - Polak, Paweł Jan (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2019)
Recenzja książki: Michał Heller, Ważniejsze niż Wszechświat, Copernicus Center Press, Kraków 2018, ss. 128.
Keywords: theology of science; G.W. Leibniz; cathegory theory in theology; paraconsistent logics